Protocol for synthesizing both racemic and chiral allenylsilanes through copper-catalyzed silylation of propargyl dichlorides - Ying Zhou; Zhengli Liu (STAR Protocols)
Summary: Chiral allenylsilanes serve as crucial intermediates in the synthesis of complex pharmaceutical molecules and natural products. Here, we present a protocol for synthesizing both racemic and chiral allenylsilanes through copper-catalyzed silylation of propargyl dichlorides. We describe steps for the SN2′ propargyl silylation reaction between propargyl dichlorides and a silylboronate, followed by the purification of the products. The obtained optically active chloro-substituted allenylsilane products can be readily transformed into various useful allene derivatives, demonstrating the high synthetic value of this methodology.For complete details on the use and execution of this protocol, please refer to Liu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.